Contemporary orthodontic archwires: A literature review - M. Noori, Reyam; A. Yassir, Yassir; T. McIntyre, Grant (Al-Salam Journal for Medical Science, 2023)
Archwires are the principal force generators used in orthodontic treatment. They are one of the fixed appliances’ active components. They produce various tooth movements by interaction with brackets and buccal tubes. Recent advancements in orthodontics have resulted in a wide variety of archwire alloys with a broad spectrum of characteristics. The proper application of these wires can shorten treatment duration, improve patient comfort, and reduce chairside time. Furthermore, the need for esthetic orthodontic treatment alternatives resulted in the introduction of esthetic archwires. These innovative archwires attempt to combine both the esthetics and good clinical performance. Understanding recent